Nanopartículas poliméricas e interações com macrófagos - Bandeira, Anielle Carvalho (2016)
Nanotechnology involves the creation and use of materials, devices and systems through control of matter on the manometer scale. It has positive impact on medicine involving the treatment and diagnosis. Drug delivery systems prepared with nanostructures have the ability to overcome biological barriers and optimizing drug release. However, one of the main challenges in the use of these systems is their internalization by macrophages. This study aims to prepare and characterize polymer nanoparticles formed by biodegradable polymers and investigate its impact on the function of macrophages in vitro by the observation of cell viability, phagocytic activity and cytokine production. Also, was investigate the cytokine profile in serum and splenocytes culture supernatant from Balb/C mice injected with chitosan nanoparticles. The chitosan and chitosan-containing magnetic nanoparticles were prepared by ionic gelation crosslinking, resulting in a morphology "nearly spherical" and positive zeta potential. The PLGA prepared by emulsification and solvent evaporation method presented spherical morphology and negative zeta potential. All preparations had a diameter smaller than 300 nanometers and polydispersity index lower than 0.5. Nanoparticles of chitosan and PLGA affected the viability of macrophages in vitro only at the highest concentration tested (4 mg/mL). The chitosan nanoparticles containing magnetic nanoparticles were internalized by macrophages after 4h and 24h of incubation. Different nanoparticles triggered high production of TNF- and low IL12p40 production and IL-10. Serum and splenocytes culture supernatant was observed in both the production of IFN- as IL-4. However, IL-4 production was higher than that of IFN-.